Alternative solution via car window filming implementation to combat global warming and resulted benefits around geographic Europe and the European Union - (:unkn) unknown (INDERSCIENCE ENTERPRISES LTD, 2016)
It is aimed to reduce fuel consumption and vehicle-sourced emissions, combat global warming and contribute to the economy via car window film implementation. Mobile air conditioning (MAC) usage in summer increases fuel consumption and vehicle emissions, which has global economic and health impacts. In summer, films block solar radiation into cabin, reduce peak temperature, hence, MAC consume less energy. Film implementation of three different types, on tinted and clear rear and side windows with clear and 20% shaded windshield of the parked passenger cars for Geographic Europe (GE) and European Union (EU) are analysed. Regarding GE, 50 countries, and EU, 28 member countries, the best possibility decreases sum of diesel and gasoline fuel consumption by 3.6 and 2.8 billion litres, reduces the passenger car sourced total GHG emissions by 34 and 27 billion kg and contributes to the economy by 5-year net savings of 270 and 226 billion $, respectively.
Keywords: car window filming; vehicle emission reduction; car window tinting; car soak temperature; mobile air conditioning; MAC; greenhouse gases; GHGs; emission economy; THERMAL COMFORT; COMPARTMENT; EMISSIONS